Using Cooperative Integrated Reading and Composition (CIRC) Technique in Teaching Reading Comprehension - Syaifullah; Asmirawati (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2025)
The students have lack of the vocabulary, difficult to identify the main idea, supporting idea, factual information of the text and guessing meaning of the word. The purpose of this activity was to explain whether CIRC technique can better improve students’ reading comprehension and to identify the factors that influence the changing of students’ reading comprehension. In addition, the kind of the community service was an action in teaching and learning process, reading comprehension by using CIRC. Moreover, the result of this activity was the students reading comprehension has improved from activity I to activity II. The score of students in activity I was 70.16 and activity II was 84.38. The improvement was 14.22 point. It concluded that the students’ reading comprehension has improved significantly by using Cooperative Integrated Reading and Composition (CIRC) Technique.